Extremely (54)Cr- and (50)Ti-rich presolar oxide grains in a primitive meteorite: Formation in rare types of supernovae and implications for the astrophysical context of solar system birth. - Nittler, Larry R. (Astrophys J Lett, 2018)
We report the identification of 19 presolar oxide grains from the Orgueil CI meteorite with substantial enrichments in (54)Cr, with (54)Cr/(52)Cr ratios ranging from 1.2 to 56 times the solar value. The most enriched grains also exhibit enrichments at mass 50, most likely due in part to (50)Ti, but close-to-normal or depleted (53)Cr/(52)Cr ratios. There is a strong inverse relationship between (54)Cr enrichment and grain size; the most extreme grains are all <80 nm in diameter. Comparison of the isotopic data with predictions of nucleosynthesis calculations indicate that these grains most likely originated in either rare, high-density Type Ia supernovae (SNIa), or in electron-capture supernovae (ECSN) which may occur as the end stage of evolution for stars of mass 8−10 M(⊙). This is the first evidence for preserved presolar grains from either type of supernova. An ECSN origin is attractive since these likely occur much more frequently than high-density SNIa, and their evolutionary timescales (~20 Myr) are comparable to those of molecular clouds. Self-pollution of the Sun’s parent cloud from an ECSN may explain the heterogeneous distribution of n-rich isotopic anomalies in planetary materials, including a recently reported dichotomy in Mo isotopes in the solar system. The stellar origins of three grains with solar (54)Cr/(52)Cr, but anomalies in (50)Cr or (53)Cr, as well as of a grain enriched in (57)Fe, are unclear.